Kidney Disease and Transplantation - Trivedi, H.L.; Nigam, Lovelesh; vanikar, aruna; shah, veena; Shah, Mamta; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Kidney Disease and Transplantation is no longer accepting submissions and will not be published by BioMed Central as of May 2017.
Keywords: Nephrology; Surgical transplantation; Nephrology; Transplant Surgery